Knowledge, attitudes and practices relating to HIV self-testing following its introduction in the Bas-Sassandra region of Côte d’Ivoire: the case of the ATLAS project - Arlette Simo Fotso; Christian Koukobo; Romain Silhol; Arsène Kouassi Kra; Marie-Claude Boily; Anthony Vautier; Joseph Larmarange (PLoS ONE, 2026)
Background Awareness of HIV status is crucial for accessing HIV care and prevention but remains suboptimal in West Africa. The ATLAS initiative, launched in Côte d’Ivoire, Mali, and Senegal, addressed this gap by distributing approximately 380,000 HIV self-testing (HIVST) kits from 2019 to 2021, primarily to key populations and their social networks. This study assessed levels and correlates of Knowledge, Attitudes, and Practices (KAP) related to HIVST in the Bas-Sassandra region of Côte d’Ivoire following ATLAS’s introduction. Method A cross-sectional population-based survey was conducted in the Bas-Sassandra region in 2021 among individuals aged 15–49. A total of 6,271 people (3,203 men and 3,068 women) were interviewed. They were selected using a three-stage stratified sampling approach in the Bas-Sassandra region. Bivariate statistics and multivariable logistic regressions were used to assess KAP levels and the associated factors. Results Although few participants reported having heard about HIVST (11%) or having used it (3%), most of them reported that if it were freely available, they would be interested/very interested in using it for themselves (76%), as well as for their sexual partners (75%). Education and wealth were positively associated with knowledge and positive attitudes towards HIVST among both men and women, whereas age was positively correlated to knowledge and use of HIVST among men only. The number of sexual partners over the last 12 months was positively associated with knowledge of HIVST and willingness to use HIVST for themselves or their sexual partners among both sexes. We also found that high HIV-related knowledge and low levels of negative attitude were positively associated with positive attitudes towards HIVST, while exposure to the media appeared to be correlated to knowledge of HIVST. Conclusion The high level of positive attitudes towards HIVST calls for a scaling up of access to HIVST in the region. Specific attention to groups with the worst KAP, such as the less educated, the poor or those with more HIV-related negative attitude, could enhance the success of such initiatives.